(untitled) (Annals of Medical Research, 2022)
Aim: The aim of this study is to evaluate the preoperative characteristics and postoperative results of cerebral arteriovenous malformations (cAVM) cases that we treated endovascularly. Endovascular embolization has started to be used as an adjuvant therapy to other treatments in the treatment of cAVM. However, with the increase of technical developments and professional experience over time; endovascular techniques have started to be the primary treatment method in the treatment of AVMs. Materials and Methods: Complaints, angiographic evaluation and treatment data of 12 patients with cAVM who were treated with endovascular methods between January 2018 and December 2020 were retrospectively reviewed. Results: Eight of the patients (66.6%) were male and 4 (33.3%) were female. AVM localizations were cerebral in eleven (91.6%) patients and cerebellar in one (8.3%) patient. According to the Spetzler-Martin grading system; 5 cases (41.6%) were classified as grade 2, 4 cases (33.3%) as grade 3, 2 cases (16.6%) as grade 4 and 1 case (8.3%) as grade 5. During the endovascular treatment procedure, iatrogenic rupture occurred in the AVM nidus in one patient. No other intraoperative or postoperative complications developed in any of the other cases. Total thrombosis was achieved in 5 cases (41.6%) and partial thrombosis in 7 cases (58.3). These 7 cases with partially thrombosis achieved (58.3%), were referred to radiosurgery after endovascular procedure. Total thrombosis was seen in 3 of these 7 patients (42.8%) after radiosurgery. The total thrombosis rate in all cases was 66.6% (n:8). The mean follow-up period was 23.8 months (12-40). Conclusion: Therapeutic embolization may be a viable option for cAVMs in selected cases. In complex cAVM cases, embolization is thought to provide a high rate of thrombosis or excision of the lesions, reducing the risks of bleeding and other complications before surgical treatment or radiosurgery.